Financial stability of European insurance companies during the COVID-19 pandemic - Karolina Puławska (Journal of Risk and Financial Management, 2021)
The European Insurance and Occupational Pensions Authority suggests that as the coronavirus disease 2019 (COVID-19) pandemic has caused significant disruption to the economy, businesses, and people's lives, national supervisory authorities should mitigate the pandemic's impact on the European insurance sector. The functioning of insurance companies is in danger as they must balance a drastic increase in the number of claims with their capital and solvency stability. In this study, we evaluate the effects of the COVID-19 pandemic on insurance companies using European insurance companies' financial statement data from 2010 to 2020. The results unambiguously demonstrate that the pandemic has negatively affected the functioning of the insurance sector. In particular, the return on assets decreased in German and Italian insurance companies during the pandemic. Furthermore, the solvency ratio decreased in the Belgian, French, and German insurance sectors. Conversely, the Polish insurance sector was unaffected. Moreover, we did not find any effects on the Z-score ratio in our sample. Lastly, the value of receivables owed to Belgian insurance companies increased. Based on this evidence, we argue that European legislators should discuss how to manage the probable financial problems of insurance companies during the COVID-19 pandemic.
Keywords: 330; COVID-19; Europe; financial stability; insurance companies; solvency; Z-score